Philosophy as a way of life and the nature of the political:: The ‘problem of Socrates’ in Leo Strauss’ thought - Makris, Spiros (Dia-noesis: A Journal of Philosophy, 2024)
The theologico-political problem has marked Leo Strauss’ engagement with the question of the Western political thought from Plato onwards. Strauss brings to the fore the relationship between vita contemplativa and vita activa or the relationship between the philosopher-citizen and the city and in this sense, the question concerning the life of Socrates in ancient Athens as well as the meaning of the Socratic phenomenon itself. It is no exaggeration to claim that Strauss’ oeuvre can be regarded as an intellectual endeavor on Socrates’ presence in the Athenian agora as the ideal exemplification of a philosophical way of life within a political community.